PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO DENGAN ADOBE CAPTIVATE MENGGUNAKAN MODEL ADDIE PADA MATERI RIAS FANTASI - Chasanah, Kurnia Uswatun; Leksono, Ibut Priono; Atiqoh, Atiqoh (Jurnal Sains dan Teknologi, 2023)
This study uses video-based learning media that can be accessed on each student's laptop or PC in exe form which can be easily accessed. The development procedure applied in the development of learning media using Adobe Captivate uses the ADDIE development model. The ADDIE model has 5 stages, namely (Analyze, Design, Development, Implementation, Evaluation). The data collection instruments used in developing video-based interactive learning media using Adobe Captivate include questionnaires and media feasibility test instruments which include validators or material experts, media experts, and design experts so that they can produce an assessment of the development of learning media. The results of the assessment given by the expert validator are (1) the validation results of the design experts are 4.55 and a percentage of 91% are in the Very Eligible category, (2) the validation results of media experts are 4.63 and the percentage is 92.6% in the Very Eligible category, and (3) material expert validation results of 3.9 and a percentage of 78% in the Eligible category. In addition to validation from experts, tests were also carried out on small and large groups. For the small group test it is 4.1 and the percentage is 82% with the Very Eligible category, while the results for the large group test are 4 and the percentage is 80% with the Feasible category.